Maternal Influenza and Offspring Neurodevelopment - Marya Egorova; Vladimir Egorov; Yana Zabrodskaya (Current Issues in Molecular Biology, 2024)
This review examines the complex interactions between maternal influenza infection, the immune system, and the neurodevelopment of the offspring. It highlights the importance of high-quality studies to clarify the association between maternal exposure to the virus and neuropsychiatric disorders in the offspring. Additionally, it emphasizes that the development of accurate animal models is vital for studying the impact of infectious diseases during pregnancy and identifying potential therapeutic targets. By drawing attention to the complex nature of these interactions, this review underscores the need for ongoing research to improve the understanding and outcomes for pregnant women and their offspring.